Faktor-Faktor yang Mempengaruhi Perilaku Petani dalam Pengendalian Hama dan Penyakit Tumbuhan melalui Analisis Jalur - Sunarru Samsi Hariadi (Jurnal Perlindungan Tanaman Indonesia, 2006)
The objective of the research was to know the factors influencing farmers' behavior in pest and disease control. Different control methods were practiced by farmers, such as resistant varieties, cultural techniques, biological control, and chemical control. In thisresearch, a survey method was used, total of farmer respondents were 60 people. Results of the research showed that factors influencing farmers' behavior in pest and disease control were age, perception, and work motivation. The increasing age of the farmers resulted better behavior in pest and disease control. A better perception of farmers towards pest and disease control, resulted better behavior in pest and disease control. The increasing work motivation of farmers, resulted better behavior in pest and disease control. Therefore, agricultural extension methods had to be developed by Field Extension Workers to increase work motivation and perception of famers, especially through farmer groups. Agricultural extension activities were best not only to increase farmers' knowledge, but also ability to control plant pest and disease, by using participal method in pleasure situation.